PENGETAHUAN DAN PERSEPSI MASALAH KESEHATAN KERJA DENGAN PERILAKU PENGGUNAAN APD DI PUSKESMAS SIMALINGKAR B - Heni Triana; Suherni Suherni (Jurnal Online Keperawatan Indonesia, 2021)
Puskesmas as a health service unit must always improve the quality of service, this can be achieved by thinking about the aspects of occupational health and safety for health workers The formulation of the problem in this study is whether there is a relationship between knowledge and perceptions of occupational health problems with the behavior of using personal protective equipment at the Simalingkar B Health Center. This type of research is analytic observational with cross sectional design. The research is located at Puskesmas Simalingkar B. The research population is all nurses on duty at Puskesmas Simalingkar B, totaling 50 people. The sample size was determined by total sampling, namely all nurses on duty at the Simalingkar B Health Center as many as 50 people. Data analysis used univariate and bivariate with Chi Square. The results showed that the majority of knowledge about the use of APD at the Simalingkar B Health Center was poor as many as 17 people (34.0%) and those who had good knowledge but did not use APD were 5 people (10.0%) there is no relationship between knowledge and the use of APD. The conclusion is that there is a relationship between perceptions and the behavior of using APD at the Simalingkar Community Health Center B. It is recommended that health workers emphasize knowledge of personal protective equipment (APD) and the benefits of safe work behavior.